2009
DOI: 10.1002/jsfa.3716
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of eight tea (Camellia sinensis) cultivars in China by elemental fingerprint of their leaves

Abstract: BACKGROUND: Tea is an infusion made from dried leaves of tea (Camellia sinensis) and can be a good dietary source of essential trace metals for humans. Therefore, it is necessary to consider variations in element content of tea leaves among tea cultivars. Thus, elemental fingerprint techniques, based on elemental contents (Al, B, Ca, Cd, Co, Cr, Cu, Fe, K, Mg, Mn, Na, P, Pb, and Zn) determined by inductively coupled plasma atomic emission spectrometry (ICP-AES) and multivariate statistical analysis, have been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
53
2
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 100 publications
(67 citation statements)
references
References 17 publications
(34 reference statements)
10
53
2
2
Order By: Relevance
“…Results for Mn presented in our study are generally comparable to those reported by Chen et al (2009), Colak et al (2005, Dash et al (2008), Narin et al (2004a, Malik et al (2008), McKenzie et al (2010) and Nookabkaew et al (2006). Concentrations of Fe in slim teas are very similar to those obtained by Aksuner et al (2012), Colak et al (2005), Kara (2009) andMcKenzie et al (2010), but higher than those determined by Chen et al (2009), Matsuura et al (2001 and Narin et al (2004b). Contents of Zn found in this work are consistent with the findings of Matsuura et al (2001) and Xie et al (1998).…”
Section: −1supporting
confidence: 92%
See 4 more Smart Citations
“…Results for Mn presented in our study are generally comparable to those reported by Chen et al (2009), Colak et al (2005, Dash et al (2008), Narin et al (2004a, Malik et al (2008), McKenzie et al (2010) and Nookabkaew et al (2006). Concentrations of Fe in slim teas are very similar to those obtained by Aksuner et al (2012), Colak et al (2005), Kara (2009) andMcKenzie et al (2010), but higher than those determined by Chen et al (2009), Matsuura et al (2001 and Narin et al (2004b). Contents of Zn found in this work are consistent with the findings of Matsuura et al (2001) and Xie et al (1998).…”
Section: −1supporting
confidence: 92%
“…Narin et al (2004b) established that the concentration of Zn in black tea produced in Turkey was within the range of 110-146 μg g −1 . In the case of Cu, our results are close to values found in teas by Aksuner et al (2012), Chen et al (2009), Colak et al (2005, Kara (2009) and Soylak et al (2007) and are significantly lower than those reported by Malik et al (2008) and Salahinejad and Aflaki (2010).…”
Section: −1supporting
confidence: 81%
See 3 more Smart Citations